2013
DOI: 10.4236/jct.2013.43089
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Urinary Engrailed-2 Levels to Tumour Volume and Pathological Stage in Men Undergoing Radical Prostatectomy

Abstract: The aim of this study was to assess the relationship between pre-prostatectomy urinary Engrailed-2 (EN2), a transcription factor secreted by prostate cancer cells, with tumour volume and pathological characteristics in resected prostate specimens. First pass urine samples (10 ml) without prior prostatic massage were collected and stored at -80˚C. EN2 levels were measured using an enzyme-linked immunoabsorbent assay. Tumour volume in the prostatectomy specimens was determined histologically. 57 men undergoing R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…Most relevant from the diagnostic point of view is the fact that EN2 can be found in urine, the less invasive liquid biopsy, wherein its levels have been shown to be elevated in PCa patients compared to controls [20,21,22,23,24]. In particular, Morgan et al demonstrated that patients with PCa had 10-fold increased urine EN2 levels compared to controls, showing a specificity of 88% to diagnose PCa [20], which suggested the putative utility of urine EN2 levels as a novel non-invasive PCa biomarker.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most relevant from the diagnostic point of view is the fact that EN2 can be found in urine, the less invasive liquid biopsy, wherein its levels have been shown to be elevated in PCa patients compared to controls [20,21,22,23,24]. In particular, Morgan et al demonstrated that patients with PCa had 10-fold increased urine EN2 levels compared to controls, showing a specificity of 88% to diagnose PCa [20], which suggested the putative utility of urine EN2 levels as a novel non-invasive PCa biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Morgan et al demonstrated that patients with PCa had 10-fold increased urine EN2 levels compared to controls, showing a specificity of 88% to diagnose PCa [20], which suggested the putative utility of urine EN2 levels as a novel non-invasive PCa biomarker. Indeed, the same group validated these results by using patients with high risk of PCa included in the IMPACT cohort [21], and later correlated the urinary levels of EN2 with tumor stage and volume in patients treated with radical prostatectomy (first-pass and midstream urine samples were evaluated) [22,23]. However, a subsequent study by Marszałł et al did not find different urinary levels of EN2 between patients with and without PCa when using complete urine samples, although they found higher EN2 urinary levels in urine after prostate massage [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of EN2 in urine was highly predictive of prostate cancer, with a sensitivity of 66% and specificity of 88.2% [ 15 ]. A linear relationship between urinary EN2 and prostate cancer volume has been demonstrated, along with a relationship between urinary EN2 and tumour stage [ 16 , 17 ]. Elevated levels of urinary EN2 have also been detected in patients with urothelial bladder cancer, with an overall sensitivity of 82% and specificity of 75% [ 18 ].…”
Section: Introductionmentioning
confidence: 99%